Nano Formulations of Natural Compounds for Enhanced Delivery - Alam, Zahangir (Journal of Diseases, 2017)
Natural products were always the key elements in ancient history that are promising to treat various diseases including cancer and prevent any health disorders. They have seen a breakthrough since they were used in cancer chemotherapy and prevention with selective phytochemicals. Fruits and vegetables contain nutrient constituents that are bioactive in disease states. Extensive in vitro and in vivo research data is available to prove their efficacy. While few compounds have successfully transitioned to the clinical trials, few of them are still facing problems due to their poor bioavailability and lack of targeting. The lack of efficacy in human studies can be attributed to the complexity of the biological system and complexity of food. In recent years, identification of molecular targets made it necessary to develop efficient formulations for delivery. Nano formulations such emulsions, nanoparticles and nano vesicles are few of the advancements that showed promising faith in natural product chemotherapy. This paper reviews few of the techniques employed for natural compound delivery which can be applied to various compounds.